Third-harmonic generation from Mie-type resonances of isolated all-dielectric nanoparticles - Melik-Gaykazyan, Elizaveta V.; Shcherbakov, Maxim R.; Shorokhov, Alexander S.; Staude, Isabelle; Brener, Igal; Neshev, Dragomir N.; Kivshar, Yuri S.; Fedyanin, Andrey A. (Philosophical Transactions of the Royal Society A-Mathematical Physical and Engineering Sciences, 2017)
Subwavelength silicon nanoparticles are known to support strongly localized Mie-type modes, including those with resonant electric and magnetic dipolar polarizabilities. Here we compare experimentally the efficiency of the third-harmonic generation from isolated silicon nanodiscs for resonant excitation at the two types of dipolar resonances. Using nonlinear spectroscopy, we observe that the magnetic dipolar mode yields more efficient third-harmonic radiation in contrast to the electric dipolar (ED) mode. This is further supported by full-wave numerical simulations, where the volume-integrated local fields and the directly simulated nonlinear response are shown to be negligible at the ED resonance compared with the magnetic one. This article is part of the themed issue 'New horizons for nanophotonics'.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Mie scattering; Nonlinear optics; Optical magnetism; Silicon nanoparticles; Third-harmonic generation